Моделі і задачі досліджень циклічного процесу електроспоживання - Щербак, Т.Л. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
The mathematical models of process of a power consumption for regular and not regular modes are offered which derivate the whole cycle of tasks theoretical, imitating and experimental. A number(line) of such tasks is given, among which it is necessary to allocate tasks of statistical data processing of measurements of process.